Hubungan Behavior Change Technique (BCT) Dengan Kepatuhan Minum Obat Pada Pasien Hipertensi Di Klinik Jelita Banjarmasin - Wahyunita, Sari; Kurniawan , Guntur; Sari , Tri Yusna; Rosyad, Muhammad Ihsan (Universitas Borneo Lestari, 2026)
Hypertension is a chronic disease with a high prevalence and requires long-term medication adherence to maintain controlled blood pressure. However, patient adherence levels remain low. Behavior Change Technique (BCT) is used as a behavioral change approach to improve medication adherence. This study aims to determine the level of medication adherence among hypertensive patients, the implementation of BCT, and the relationship between BCT and medication adherence at Jelita Clinic Banjarmasin. The design cross sectional, with a sample of 33 uncontrolled hypertensive patients. The research instruments included the MMAS-8 questionnaire to assess adherence and the Taxonomy v1 questionnaire for BCT intervention. Data were analyzed using the korelasi test. The results in the m adherence improved to 67% in the moderate category and 33% in the low category. In addition, hypertension classification showed improvement after the intervention. The korelasi test obtained a value of r = 0.485 with p = 0.004, indicating a significant and moderately strong relationship between BCT and medication adherence. It can be concluded that the Behavior Change Technique (BCT) is effective in improving patients' adherence to antihypertensive medication and contributes to better blood pressure control.